FURTHER OBSERVATIONS ON THE FISHERY AND BIOLOGY OF’CHOODAI’ (SARDINELLA spp.) OF MANDAPAM AREA - Bennet, P Sam (Indian Journal of Fisheries, 2011)
THE sardines, locally called Choodai, constitute one of the important groupsof fishes supporting the fisheries of the Mandapam area. Sardinella albellaand Sardinella gibbosa are the two important species forming the fishery.Previous studies on sardines in the area include observations made byDevanesan (1932) on the food and feeding habits and Chacko (1946) on thebionomics of S. gibbosa. Investigations have been in progress since 1952at the Central Marine Fisheries Research Station (Sekharan, 1955 and 1959)on the Choodai fishery. The present study was undertaken from May 1958to March 1960 as a continuation of the work.